Is There a “Right” Amount of Oxygen for Preterm Infant Stabilization at Birth? - Oei, Ju Lee; Vento, Maximo (Frontiers in Pediatrics, 2019)
The amount of oxygen given to preterm infants within the first few minutes of birth is one of the most contentious issues in modern neonatology. Just two decades ago, pure oxygen (FiO2 1.0) was standard of care and oximetry monitoring was not routine. Due to concerns about oxidative stress and injury, clinicians rapidly adopted the practice of using less oxygen for the respiratory support of all infants, regardless of gestational maturity and pulmonary function. There is now evidence that initial starting fractional inspired oxygen may not be the only factor involved in providing optimum oxygenation and that the amount of oxygen given to babies within the first 10 minutes of life is a crucial factor in determining outcomes, including death and neurodevelopmental injury. In addition, evolving practice, such as non-invasive respiratory support and delayed cord clamping, need to be taken into consideration when considering oxygen delivery to preterm infants. This review will discuss evidence to date and address the major knowledge gaps that need to be answered in this pivotal aspect of neonatal practice.